Sand fly typing: a simple and morphologically-supported method based on polymorphism of 18S rRNA gene in a Leishmaniasis endemic area of Argentina - Almazán, María Cristina; Copa, Griselda Noemí; Lauthier, Juan José; Gil, José Fernando; López Quiroga, Inés; Hoyos, Carlos Lorenzo; Díaz Fernández, Melisa Evangelina; Nasser, Julio Rubén; Korenaga, Masataka; Marco, Jorge Diego; Barroso, Paola Andrea (Acta Tropica, 2020)
•The method allowed the molecular identification of sand flies from a leishmaniasis endemic area in Argentina.•Specimens that could not be determined morphologically, due to inappropriate mounting, were successfully identified by PCR-RFLP.•RFLP analyzes generated sand fly species-specific restriction patterns.•The caught sand flies are Leishmania vectors, which highlights the risk of infection in the area. Leishmaniases are vector-borne diseases that in the Americas are distributed from southern United States to northern Argentina. The vectors for this disease are small dipterans known as sand flies that are usually identified morphologically by observing structures with taxonomic value; but it is time-consuming, laborious, and requires entomological expertise. Then, this work was aimed at identifying sand flies with molecular techniques, using the morphological identification as a reference technique, in an endemic area of American Tegumentary Leishmaniasis (ATL) located in northern Argentina. For this, sand flies were caught at two patches of vegetation adjacent to rural areas in Orán department, Salta Province. Females were dissected with sterile needles; the head and last abdominal segments were analyzed for morphological identification. The remaining thorax and abdominal segments were used to extract DNA, which was amplified by PCR of the small subunit (SSU), 18S rRNA gene. PCR products were digested with CviQI and DdeI enzymes to identify sand fly species by Restriction Fragment Length Polymorphism (RFLP) analysis. Thus, the restriction pattern of each caught species was defined according to morphological identification. A total of 1501 females, belonging to four sand fly species, were captured. Nyssomyia neivai (1347/1501) was the most abundant species, followed by Migonemyia migonei (90/1501). From the total, 801 females were morphologically and molecularly identified, while 700 females were characterized only molecularly. For those females analyzed by both methods, there was total coincidence in the achieved result. Besides, the 5% (38/801) of females that could not be determined morphologically due to inadequate mounting were molecularly identified. All the females characterized just by PCR-RFLP, were successfully identified. Our results indicate that the explored method is capable of identifying the sand fly species that circulate in an ATL endemic area. Since this method is based on the analysis of markedly different patterns, the identification process might be more easily reproduced, as the bias introduced by the technician's lack of experience is removed. [Display omitted]